Effective Ligand Engineering of the Cu2ZnSnS4 Nanocrystal Surface for Increasing Hole Transport Efficiency in Perovskite Solar Cells. (26th September 2016) - Khanzada, Laraib Sarfraz; Levchuk, Ievgen; Hou, Yi; Azimi, Hamed; Osvet, Andres; Ahmad, Rameez; Brandl, Marco; Herre, Patrick; Distaso, Monica; Hock, Rainer; Peukert, Wolfgang; Batentschuk, Miroslaw; et al.
Abstract : Effective engineering of surface ligands in semiconductor nanocrystals can facilitate the electronic interaction between the individual nanocrystals, making them promising for low‐cost optoelectronic applications. Here, the use of high purity Cu2 ZnSnS4 (CZTS) nanocrystals as the photoactive layer and hole‐transporting material is reported in low‐temperature solution‐processed solar cells. The high purity CZTS nanocrystals are prepared by engineering the surface ligands of CZTS nanocrystals, capped originally with the long‐chain organic ligand oleylamine. After ligand removal, CZTS nanocrystals show substantial improvement in photoconductivity and mobility, displaying also an appreciable photoresponse in a simple heterojunction solar cell architecture. More notably, CZTS nanocrystals exhibit excellent hole‐transporting properties as interface layer in perovskite solar cells, yielding power conversion efficiency (PCE) of 15.4% with excellent fill factor (FF) of 81%. These findings underscore the importance of removing undesired surface ligands in nanocrystalline optoelectronic devices, and demonstrate the great potential of CZTS nanocrystals as both active and passive material for the realization of low‐cost efficient solar cells. Abstract : Effective ligand engineering of Cu2 ZnSnS4 (CZTS) nanocrystal surface is demonstrated to lead to improvement of the electrical properties of the thin film. Furthermore, surface‐modified CZTS nanocrystals exhibit excellent hole transporting properties as the interface layer in a perovskite solar cell. The perfomance of perovskite devices is shown to vary from 12.2% to 15.4% as a function of ligand removal.